Computer supported qualitative research - Costa, António Pedro; Reis, Luís Paulo, 1970-; Neri de Sousa, Francislê; Moreira, António; Lamas, David (Springer, 2016)
This book contains an edited selection of the papers accepted for presentation and discussion at the first International Symposium on Qualitative Research (ISQR2016), held in Porto, Portugal, July 12th-14th, 2016. The book and the symposium features the four main application fields Education, Health, Social Sciences and Engineering and Technology and seven main subjects: Rationale and Paradigms of Qualitative Research (theoretical studies, critical reflection about epistemological dimensions, ontological and axiological); Systematization of approaches with Qualitative Studies (literature review, integrating results, aggregation studies, meta -analysis, meta- analysis of qualitative meta- synthesis, meta- ethnography); Qualitative and Mixed Methods Research (emphasis in research processes that build on mixed methodologies but with priority to qualitative approaches); Data Analysis Types (content analysis , discourse analysis , thematic analysis , narrative analysis , etc.); Innovative processes of Qualitative Data Analysis (design analysis, articulation and triangulation of different sources of data - images, audio, video); Qualitative Research in Web Context (eResearch, virtual ethnography, interaction analysis , latent corpus on the internet, etc.); Qualitative Analysis with Support of Specific Software (usability studies, user experience, the impact of software on the quality of research.
Includes author index.
Keywords: Qualitative research -- Data processing -- Congresses.; elektronické knihy; electronic books